The role of human capital in the digital transformation economy - Trần, Nhật Thiện (TNU Journal of Science and Technology, 2024)
This paper aims to study the role of human capital accumulation in the growth of the digital transformation economy by investigating the interplay between human capital formation and the effects of tax policies from government spending on human beings. The research methodology is based on endogenous growth theory with an overlapping generation model and homogeneous economic agents. The main finding is that public investment in enhancing the efficiency of workers results in the economic growth of the digital transformation economy. Another is that two effects of taxation are noteworthy: (i) taxes reduce households' income, lowering their investment in physical capital, which hurts output; (ii) taxation raises the public spending on human capital, thus enhancing the efficiency of labor capacity, consequently, increasing economic growth in digital transformation economy. The study's conclusion is that the long-run growth rate is fueled by the investment in human capital, and the government may levy taxes on labor income and capital returns to finance this public investment.